Quality of drug information on the World Wide Web and strategies to improve pages with poor information quality: an intervention study on pages about sildenafil - Martin-Facklam, Meret; Kostrzewa, Michael; Martin, Peter; Haefeli, Walter E. (British journal of clinical pharmacology, 2004)
Aims The generally poor quality of health information on the world wide web ( WWW) has caused preventable adverse outcomes. Quality management of information on the internet is therefore critical given its widespread use. In order to develop strategies for the safe use of drugs, we scored general and content quality of pages about sildenafil and performed an intervention to improve their quality. Methods The internet was searched with Yahoo and AltaVista for pages about sildenafil and 303 pages were included. For assessment of content quality a score based on accuracy and completeness of essential drug information was assigned. For assessment of general quality, four criteria were evaluated and their association with high content quality was determined by multivariate logistic regression analysis. The pages were randomly allocated to either control or intervention group. Evaluation took place before, as well as 7 and 22 weeks after an intervention which consisted of two letters with individualized feedback information on the respective page which were sent electronically to the address mentioned on the page. Results Providing references to scientific publications or prescribing information was significantly associated with high content quality (odds ratio: 8.2, 95% CI 3.2, 20.5). The intervention had no influence on general or content quality. Conclusions To prevent adverse outcomes caused by misinformation on the WWW individualized feedback to the address mentioned on the page was ineffective. It is currently probably the most straight-forward approach to inform lay persons about indicators of high information quality, i.e. the provision of references.
Published: 16 December 2003
Gesehen am 19.05.2021